STUDENTS’ PERCEPTION OF PLAGIARISM IN THESIS WRITING - Lu’luil Maknun; Siti Nurnadiah (Jurnal Inovasi Penelitian, 2022)
The main purpose of this study was to find out the students’ perception of plagiarism and the reasons why students did plagiarism in thesis writing. The research participants were students of sixth and eight semesters of English Department at Universitas Mercu Buana Yogyakarta. It involved 38 students that were chosen by random sampling. This research was conducted by using Descriptive Qualitative-Quantitative research or known as mixed methods. The collecting data was using the instrument questionnaires and interviews. The data for students’ perception of plagiarism in thesis writing showed that 49% from the perceptual learning, 67,6% from the mental set, 51,4 % from motives and need, and the last 61% from cognitive style, revealed that most students did not understand about plagiarism in thesis writing and most of the student had negative perception and the data for the reason why students did plagiarism. It was related to Apiah, (2016), the reasons why students did plagiarism was their lack of writing abilities, achieving high grades, a lack of knowledge of plagiarism, the price of high-quality study materials, peer pressure, and family pressure. It can be concluded that most students knew about the reason why students did plagiarism.